Perioperative Bromelain Therapy after Wisdom Teeth Extraction – A Randomized, Placebo‐Controlled, Double‐Blinded, Three‐Armed, Cross‐Over Dose‐Finding Study. (6th September 2016) - Bormann, Kai‐Hendrik; Weber, Kristina; Kloppenburg, Heike; Koch, Armin; Meiser, Peter; Gellrich, Nils‐Claudius
Abstract : Reduction in postoperative edema and inflammatory reactions is the key to the posttraumatic regeneration process. Use of bromelain is well established in this indication, but there is some controversy with regard to the optimal dosing of this drug. The aim of our study was therefore to investigate the efficacy of dosage‐dependent therapy with bromelain in patients after wisdom teeth extraction by comparing the registered dosage 1000 FIP (Fédération Internationale Pharmaceutique) against higher dosages of 3000 FIP and 4500 FIP. A total of 75 patients were randomized to one of the three dosage arms, and 68 of these patients were finally analyzed in the modified intention‐to‐treat population. Patients involved underwent two surgery sessions: one study period being conducted under treatment with bromelain and the other with placebo. Postoperative swelling determined by a 3D face scanning system was defined as the primary endpoint; further efficacy parameters were maximum swelling, pain, difficulty in swallowing, and use of analgesics. A superiority of treatment with 3000 FIP and 4500 FIP versus 1000 FIP could not be demonstrated. The analysis of pooled bromelain treatments versus placebo did, however, show a clear trend in favor of bromelain for all assessments. Adverse events did not occur more frequently under bromelain therapy compared with placebo. This study thus clearly supports the clinical relevance of treatment of postoperative conditions with bromelain, and the recommended daily dose was sufficiently effective in this trial and indication. Copyright © 2016 John Wiley & Sons, Ltd.